Evaluation of the Effect of Using Educational Games on Early Childhood Learning Achievement - Nurteti, Lilis; Srisudarso, Mansyur; Wahyuni, Annisa; Ramadhan, Mariatul Kamila; Ananta, Maulana Paramaditya (Journal Emerging Technologies in Education, 2024)
Background. Early childhood from 3-5 years old is classified as a digital native generation. This is triggered by the dependence of individuals on technology. The ease of access in the form of videos and other entertainment will trigger children to do activities. This aspect will help in providing stimulation for children while parents are busy with work. The use of educational games is one form of the role of technology use on the motor and cognitive development of children. Purpose This study aims to investigate how influential the use of educational games is. Looking for shortcomings and advantages in the use of educational games to be evaluated. Educational games that present interesting animations and images will captivate children when they see them. This will make children enthusiastic and easy to remember things. Method. The method used in this research is a qualitative method. This method is a way of research that uses numbers. The data collected comes from a questionnaire distributed to teachers at an early age level. The statements presented are loaded on Google from to facilitate access from teachers without taking time. The statements presented are related to evaluating the effect of using educational games on early childhood achievement. The collected data will later be transferred to Excel. After that the data will be inputted into spss to do the oneway anova test. Results. The result of this research is the use of technology in the form of educational games will help optimize the development and growth of early childhood. However, not all educational games are able to accommodate balanced and comprehensive development. It takes the role of parents and teachers to control the use of technology in early childhood so as not to get addicted.   Conclusion This research can be concluded that the use of technology in the form of content, educational games and other things in proportion will help improve the learning achievement of children. Proper use according to portions will help without replacing the role of parents and teachers.